2021
DOI: 10.1002/ente.202100684
|View full text |Cite
|
Sign up to set email alerts
|

Small‐Molecular Crowding Electrolyte Enables High‐Voltage and High‐Rate Supercapacitors

Abstract: Aqueous energy storage devices attract increased attention due to their high safety, low cost, and easy maintenance. However, the low energy density caused by the narrow electrochemical stability window (ESW) of aqueous electrolytes severely restricts their widespread applications. Herein, a new type of “small‐molecule crowding” electrolyte of 95EG‐H2O (95 wt% ethylene glycol [EG]) is proposed for the first time. Significant enhancement of water molecular stability is accomplished through the engineering of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…3a-e 3f †). These results further indicated that a high voltage stability and high coulombic efficiency of AC-based SC with 1 M Na 2 SO 4 /H 2 O/EG electrolyte can be simultaneously obtained, which is a much better performance than that of other reported aqueous electrolytes 11,13,15,[18][19][20][21] (Table 1).…”
Section: Electrochemical Properties and Inuence Of Eg Contentmentioning
confidence: 74%
“…3a-e 3f †). These results further indicated that a high voltage stability and high coulombic efficiency of AC-based SC with 1 M Na 2 SO 4 /H 2 O/EG electrolyte can be simultaneously obtained, which is a much better performance than that of other reported aqueous electrolytes 11,13,15,[18][19][20][21] (Table 1).…”
Section: Electrochemical Properties and Inuence Of Eg Contentmentioning
confidence: 74%
“…Concurrently, the OH stretching of water at 3431 cm −1 shifted to a lower wavenumber of 3400 cm −1 (EG8), further substantiating the formation of hydrogen bonds between EG and water molecules. The interaction between EG and water molecules partially disrupts the hydrogen-bonding network among water molecules, attenuating their reactivity, which consequently diminishes the occurrence of hydrogen and oxygen evolution side reactions, thereby contributing to the enhanced stability of the electrolyte [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Molecules 2024, 29, 1393 6 of 14 occurrence of hydrogen and oxygen evolution side reactions, thereby contributing to the enhanced stability of the electrolyte [47].…”
Section: Characterization Of Nacl/h 2 O/eg Hybrid Electrolytesmentioning
confidence: 99%
“…In a neutral electrolyte, the cell voltage could be up to 2.2 V . This value could be further enhanced to 2.6 V or higher by using the water-in-salt strategy, adding small molecules to the electrolyte, or other methods. However, the electrochemical performance of electrode materials in neural electrolytes might be suppressed. For example, activated carbon (AC) in neutral electrolyte shows a specific capacitance only half of that in acid or alkaline electrolytes.…”
mentioning
confidence: 99%